The Skills Marketing Majors Believe They Acquire: Evidence From a National Survey. (December 2019) - Hartley, Phillip; Routon, P. Wesley; Torres, Luis
Drawing from a panel survey of over 400, 000 college graduates from over 600 different colleges and universities in the United States, this article addresses three questions related to skill change during college tenure. First, as judged by the students themselves, how much change in 15 skill categories do marketing majors experience during college? Second, how do these skill changes compare with those reported by other business majors and college students from all other majors? Finally, controlling for a host of relevant student and institutional characteristics, what is the impact of marketing education on the changes reported for each of these 15 skills? Findings indicate that marketing students' perceptions of their own skill developments are generally very positive, but in some cases other business majors or the broader array of college students rated themselves more favorably. Taken in combination with employers' contrasting perceptions of graduates' workforce readiness, these results have implications for the improvement of marketing curricula and course design including greater emphasis on experiential learning and other opportunities for students to apply the knowledge they gain.